Pengaruh Supervisi Kepala Sekolah Terhadap Kinerja Guru (Studi pada SMP Negeri 9 Kota Malang) - Mahindra Wisnu Putra Pratama; Mahindra Wisnu Putra Pratama (Jurnal Administrasi Publik, 2016)
Abstract: Supervision Effect on Performance Principal Teacher (Case Study on Public Junior High School 9 Malang). The study is based on education policy staternents Research and Education Ministry in 2013, frorn 879 955 prirnary school teachers in Indonesia turned out to be only about 30% eligible to teach the class in front of the students and the rest are not worth it. For junior high school teachers, high school and vocational nurnber is alrnost the sarne. It was found that there are still rnany obstacles or problerns relating to the implementation of the supervision of the school principal had a major impact on the morale of teachers. The results of this study indicate that the principal of SMPN 9 Malang is a person who is fully responsible for the organization of school activities, and mobilize all parts of the school to carry out the functions and duties which it is responsible. Principal in the division of tasks of each part of the school managernent with clear detail both the function and responsibility. With this model organizational structure of each part in school interrelated and influence each other so that the goal can be achieved according to the target school. Effect of supervision of the principal of SMPN 9 Malang significant effect on the spirit of teacher perforrnance, the effect of supervision of the school principal to teacher morale is 0.715 or 71.5% and the remaining 29.5% diperngaruhi by other variables not included in this study. The headmaster as supervisor in the lead should be adapted to the situation, a condition that occurs and the organization's needs and the needs of the school cornmunity so as to improve school performance. From the aspect of leadership roles, Principal at the school as a leader in executing its duty to lead and manage schools included in the category of success. Communication between superiors and subordinates are created with good two-way communication, in providing leadership to give guidance directing, coaching, and support to subordinates in completing its tasks. Keywords: supervision, teacher performance   Abstrak: Pengaruh Supervisi Kepala Sekolah Terhadap Kinerja Guru (Studi Pada SMP Negeri 9 Kota Malang). Penelitian ini didasarkan atas kebijakan pendidikan yang laporan Balitbang Depdiknas tahun 2014, dari 878.985 guru SD di Indonesia ternyata hanya sekitar 32% yang layak rnengajar dikelas didepan para siswa serta  yang selebihnya tidak layak. Untuk guru SMP, SMA, serta  SMK angkanya juga harnpir sarna. Diternukan bahwa rnasih ada kendala atau persoalan yang berkaitan untuk pelaksanaan supervisi pimpinan sekolah  yang berdarnpak besar terhadap sernangat kerja guru. Hasil penelitian ini rnenunjukkan bahwa kepala sekolah SMP Negeri 9 kota Malang adalah orang yang bertanggung jawab penuh terhadap penyelengaraan kegiatan sekolah, serta  rnenggerakkan sernua bagian sekolah untuk rnenjalankan tugasnya serta  tugas yang rnenjadi tanggung jawabnya. Kepala sekolah dalarn pernbagian tugas tiap-tiap bagian pengelola sekolah terinci untuk jelas baik terhadap tugasnya serta  tanggung jawabnya. Dengan struktur organisasi rnodel ini setiap bagian di sekolah rnerniliki keterkaitan serta  saling rnernpengaruhi satu untuk  yang lain sehingga tujuan sekolah dapat tercapai sesuai target. Pengaruh supervisi pimpinan sekolah  SMP Negeri 9 kota Malang memberikan pengaruh signifikan terhadap sernangat kinerja guru, besarnya pengaruh supervisi pimpinan sekolah  terhadap sernangat kerja guru adalah 0,715 atau 71,5% serta  sisanya yaitu 29,5% diperngaruhi oleh variabel lain yang tidak rnasuk dalarn penelitian ini. Kepala sekolah sebagai supervisor dalarn rnernirnpin hendaknya disesuaikan untuk situasi, kondisi yang terjadi serta  kebutuhan organisasi serta kebutuhan warga sekolah sehingga dapat rneningkatkan kinerja sekolah. Dari aspek peranan kepernirnpinan, Kepala Sekolah selaku pernirnpin di sekolah dalarn rnelaksanakan tugasnya rnernirnpin serta  rnengelola sekolah terrnasuk dalarn kategori berhasil. Kornunikasi antara atasan untuk bawahan tercipta untuk baik yaitu kornunikasi dua arah, dalarn pernberian pengarahan pirnpinan rnernberi birnbingan, pernbinaan, serta  dukungan terhadap bawahan dalarn rnenyelesaikan tugasnya.   Kata kunci: supervisi, kinerja guru